Left Ventricular Unloading Using an Impella CP Improves Coronary Flow and Infarct Zone Perfusion in Ischemic Heart Failure. Issue 6 (7th March 2018) - Watanabe, Shin; Fish, Kenneth; Kovacic, Jason C.; Bikou, Olympia; Leonardson, Lauren; Nomoto, Koichi; Aguero, Jaume; Kapur, Navin K.; Hajjar, Roger J.; Ishikawa, Kiyotake
Abstract : Background: Delivering therapeutic materials, like stem cells or gene vectors, to the myocardium is difficult in the setting of ischemic heart failure because of decreased coronary flow and impaired microvascular perfusion (MP). The aim of this study was to determine if mechanical left ventricular (LV) unloading with the Impella increases coronary flow and MP in a subacute myocardial infarction. Methods and Results: Anterior transmural myocardial infarction (infarct size, 26.0±3.4%) was induced in Yorkshire pigs. At 2 weeks after myocardial infarction, 6 animals underwent mechanical LV unloading by Impella, whereas 4 animals underwent pharmacological LV unloading using sodium nitroprusside for 2 hours. LV unloading with Impella significantly reduced end‐diastolic volume (−16±11%, P =0.02) and end‐diastolic pressure (EDP; −32±23%, P =0.03), resulting in a significant decrease in LV end‐diastolic wall stress (EDWS) (infarct: 71.6±14.7 to 43.3±10.8 kdynes/cm 2 [ P =0.02]; remote: 66.6±20.9 to 40.6±13.3 kdynes/cm 2 [ P =0.02]). Coronary flow increased immediately and remained elevated after 2 hours in Impella‐treated pigs. Compared with the baseline, MP measured by fluorescent microspheres significantly increased within the infarct zone (109±81%, P =0.003), but not in the remote zone. Although sodium nitroprusside effectively reduced LV‐EDWS, 2 (50%) of sodium nitroprusside–treated pigs developed profound systemic hypotension. A significant correlation was observed between the infarct MP and EDWS ( r 2 =0.43, P =0.03), suggesting an important role of EDWS in regulating MP during LV unloading in the infarcted myocardium. Conclusions: LV unloading using an Impella decreased EDWS and increased infarct MP without hemodynamic decompensation. Mechanical LV unloading is a novel and efficient approach to increase infarct MP in patients with subacute myocardial infarction.